The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/nyas.13036
|View full text |Cite
|
Sign up to set email alerts
|

A neural window on the emergence of cognition

Abstract: Can babies think? A fundamental challenge for cognitive neuroscience is to answer when brain functions begin and in what form they first emerge. This is challenging with behavioral tasks, as it is difficult to communicate to an infant what a task requires, and motor function is impoverished, making execution of the appropriate response difficult. To circumvent these requirements, neuroimaging provides a complementary route for assessing the emergence of cognition. Starting from the prerequisites of cognitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 168 publications
(346 reference statements)
3
10
0
Order By: Relevance
“…Our results suggest that the executive system may be important for development much earlier than previously thought ( Cusack et al, 2016 ). Injury to this system essential for learning and cognition would be expected to lead to a spectrum of neurodevelopmental deficits.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our results suggest that the executive system may be important for development much earlier than previously thought ( Cusack et al, 2016 ). Injury to this system essential for learning and cognition would be expected to lead to a spectrum of neurodevelopmental deficits.…”
Section: Discussionsupporting
confidence: 60%
“…Neuroimaging has shown that these networks are present at term-equivalent age ( van den Heuvel et al, 2014b ; Fransson et al, 2009b ), and show the greatest maturational changes in healthy term-born infants over the first two years ( Gao et al, 2015a ; Doria et al, 2010 ; Cao et al, 2016 ; Fransson et al, 2007 ; Fransson et al, 2011 ). It has, subsequently, been proposed that they might play a crucial role in infant learning and development ( Cusack et al, 2016 ), even though there is little behavioral manifestation of executive control before 5 1/2 months postnatally ( Reznick et al, 2004 ; Reynolds and Romano, 2016 ). Our third hypothesis was therefore that the functional connectivity of the frontoparietal executive network would be related to early motor learning.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that the executive system may be important for development much 321 earlier than previously thought 29 . Injury to this system essential for learning and cognition 322 would be expected to lead to a spectrum of neurodevelopmental deficits.…”
Section: Discussion 303mentioning
confidence: 56%
“…It has, 131 subsequently, been proposed that they might play a crucial role in infant learning and 132 development 29 , even though there is little behavioral manifestation of executive control before 133 5 1/2 months postnatally 30,31 . Our third hypothesis was therefore that the frontoparietal 134 executive network would be important for early motor learning.…”
Section: Neonatal Intensive Care Units (Nicus) 119mentioning
confidence: 99%
“…How behaviours relate to a conscious experience of pain is ultimately unknown. Neuroimaging provides more direct insight into the neural processes underlying infant experience 32,33 and has the potential to improve the inferences we make about pain in nonverbal populations. Multivariate fMRI signatures aim to robustly link features of brain activity to specific experiences 15,19 , and a key potential application of these signatures is to make valuable inferences in challenging patient populations with limited communication.…”
Section: Discussionmentioning
confidence: 99%